2005
DOI: 10.1055/s-2005-867060
|View full text |Cite
|
Sign up to set email alerts
|

Die „Medikamenten-Erfahrungs-Skala für Immunsuppressiva” (MESI) - erste Ergebnisse zu einem neuen Screeninginstrument in der Transplantationsmedizin

Abstract: The MESI is a short, easy-to-use screening instrument for recording the subjective experiences and attitudes of patients after an organ transplant. Of clinical significance is the correlation with compliance. Patients with a scale score of > 15 in particular should be spoken to by their treating doctor with regard to their attitudes to and experiences of the immunosuppressants, as well as with regard to their compliance behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 6 publications
0
14
0
4
Order By: Relevance
“…The recently developed Medication Experience Scale for Immunosuppressants (MESI) is a short screening instrument recording the subjective experiences and cognitive attitudes of patients vis-à-vis their immunosuppressive medication (30). The scale shows an internal consistency (Cronbach's alpha) of 0.78.…”
Section: Instrumentsmentioning
confidence: 99%
“…The recently developed Medication Experience Scale for Immunosuppressants (MESI) is a short screening instrument recording the subjective experiences and cognitive attitudes of patients vis-à-vis their immunosuppressive medication (30). The scale shows an internal consistency (Cronbach's alpha) of 0.78.…”
Section: Instrumentsmentioning
confidence: 99%
“…Patients with a cut-off-value of > 15 points present a clinical indication of the impairment of adherence. The German version of the MESI has an internal consistency (Cronbach's Alpha) of 0.78 (Goetzmann et al 2006). …”
Section: Medication Experience Scale For Immunosuppressants (Mesi)mentioning
confidence: 99%
“…The MESI (Goetzmann et al 2006) is a self-reported questionnaire for the assessment of subjective experiences and attitudes after organ transplantation. The instrument comprises seven items.…”
Section: Medication Experience Scale For Immunosuppressants (Mesi)mentioning
confidence: 99%
“…Additionally, Massey et al (2013) reported that patients who thought their graft would last longer reported higher overall adherence. Other research suggests that the converse also holds; that is, perceptions of IM as unimportant (Gheith et al 2008) and scepticism (Goetzmann et al 2006) are predictors of non-adherence. Griva et al (2012) also found that minor beliefs in medication necessity, little worry about the viability of the graft and medication-related concerns could trigger nonadherence.…”
Section: Knowledge and Beliefsmentioning
confidence: 98%